KEANEKARAGAMAN JENIS TUMBUHAN BAWAH BERPOTENSI OBAT DI KAWASAN GUNUNG TILU KABUPATEN KUNINGAN JAWA BARAT - Pebriyanty, Santy; Hendrayana, Yayan; Herlina, Nina (Jurnal Nusa Sylva, 2023)
Undergrowth is a type of basic vegetation found under forest stands except for forest tree regeneration, which includes grasses, herbs and shrubs. Undergrowth plants have a primary function in conserving soil and water. This is because the undergrowth has a large root system that produces dense clumps and is able to prevent soil erosion, as a protector of the soil from raindrops and runoff, also plays a role in increasing organic matter in the soil as green manure and mulch. Utilization of undergrowth plants as a source of medicines has an important role and is an alternative for the community to maintain health and treat a disease. The purpose of this study was to determine the diversity of undergrowth plants and to identify undergrowth plants with medicinal potential as a source of information for the community and area managers. The method used is the transect method/checkered line. Sampling plots were taken in 3 routes, namely the Citambelang, Ebeg-ebeg, and Bakukung routes. Each path consists of 9 sample plots. The results of the undergrowth inventory were then calculated the Important Value Index (IVI) and Species Diversity Index (H' The results showed that there were 44 types of undergrowth found in the Gunung Tilu area from 31 families with a total of 668 individuals.  The largest IVI was found in cakar ayam (Selaginella doerderleinii) with a value of 22.64 and the smallest IVI was for kemukus (Piper cubeba) and meniran (Phyllanthus urinaria) with a value of 0.88. For undergrowth plants that have medicinal potential, 28 species from 23 families and 521 individuals were found. The diversity index in undergrowth in the Mount Tilu area is categorized as low with an index value (H'<1) which is 0.32. This information is very important for future management of the Mount Tilu forest area.